2017
DOI: 10.18203/2349-2902.isj20172399
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum lactic dehydrogenase, glutamic oxaloacetic transaminase, creatine phosphokinase, alkaline phospatase, serum phosphorus in the cases of bowel ischemia in acute abdomen

Abstract: Background: Bowel ischemia is a life-threatening condition which may arise from a number of causes affecting the arterial and venous compartments of the mesenteric circulation. The rapid onset of acute mesenteric ischemia and the potential rapidity with which bowel infarction may occur explain the lethality of this disease. The aim of this study was to evaluate the role of serum lactic dehydrogenase (LDH), glutamic oxaloacetic transaminase (SGOT), creatine phosphokinase (CPK), alkaline phospatase, serum phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Several clinical studies found that LDH is a useful biomarker for acute mesenteric ischemia, [ 55 , 56 ]. However, interpretation of the results may be difficult in COVID-19 patients, as both lactate and LDH were also found to be independent risk factors of severe forms of COVID-19 [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies found that LDH is a useful biomarker for acute mesenteric ischemia, [ 55 , 56 ]. However, interpretation of the results may be difficult in COVID-19 patients, as both lactate and LDH were also found to be independent risk factors of severe forms of COVID-19 [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…LDH levels were found to have increased to 623 U/L in AMI patients in the COVID-19 period 16 . Serum AST values were found to be significantly higher in patients with intestinal ischemia when compared to those who did not have intestinal ischemia 29 . It was also reported that serum AST levels were increased during the COVID-19 infection due to both increased viral load and tissue hypoperfusion 30 .…”
Section: Discussionmentioning
confidence: 83%